Some anatomical and technological characteristics of 24 Quercus wood species (oaks) of Mexico - Pérez-Olvera, Carmen de la Paz; Dávalos-Sotelo, Raymundo (Instituto de Ecología, A.C., 2016)
The anatomical, physical and mechanical characteristics of 24 Quercus species of the Lobatae section (red oaks) and of the Quercus section (white oaks) collected in several states of the Mexican Republic are presented. The sample consisted of one to five specimens per species growing in pineoak forests. For the macroscopic anatomical study 12 x 7 x 1 cm specimens were used and slides with views of the different planes as well as the dissociated material were made for the microscopic study. For the physical and mechanical studies, specimens of different sizes were made, according to ASTM standards. All the material was prepared in the different planes: transverse, tangential and radial. Descriptive statistics were calculated for each variable measured and the different properties were classified into categories according to their mean values. Tests were made with small clear green specimens. Based on bibliography, information on other characteristics is included. According to the results obtained, end uses for the woods are suggested.